Una Revisión Crítica del Sistema Interamericano de Derechos Humanos: Pasado, Presente y Futuro - Gallón Giraldo, Gustavo; Monzón Cifuentes, Luz Marina; Gómez Camacho, Juan José; Grossman, Claudio; Goldman, Robert K.; Martin, Claudia; Rodríguez-Pinzón, Diego; Krsticevic, Viviana; Nikken, Pedro; Pinto, Mónica; Vannuchi, Paulo (Anuario de Derechos Humanos, 2007)
.